The effect of Moringa vegetable + small eggplant therapy on increasing the blood hemoglobin levels of pregnant women in the working area of ​​the Lamparinga Health Center, North Konawe Regency - Rosniwati, Rosniwati; Tasnim, Tasnim; Asri, Andi (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Pregnancy is a vulnerable period for anemia due to iron deficiency. The prevalence of anemia in pregnant women at the Lamparinga Community Health Center was 26.88% in 2020, 41.17% in 2021, and 57.14% in 2022. Consuming moringa leaves is an alternative to address anemia. Variation therapy with moringa and local vegetables is crucial for pregnant women to support increased hemoglobin levels. This study aims to determine the effect of moringa and small eggplant therapy on increasing hemoglobin levels in pregnant women in the Lamparinga Community Health Center, North Konawe Regency. Method:Using quantitative research, a pre-test, post-test, one-group design was used. The population was all pregnant women in the Lamparinga Community Health Center working area from 2024 until March, totaling 32 people. A sample of 25 people was selected using simple random sampling. Result:Using the paired t-test, a p value of 0.001 was obtained for moringa + eggplant on increasing blood hemoglobin levels of pregnant women in the working area of ​​the Lamparinga Health Center, North Konawe Regency. Conclusion:Moringa and small eggplant therapy has been shown to increase hemoglobin levels in pregnant women. Pregnant women are advised to regularly consume locally sourced foods, including green vegetables and fruits, to increase their hemoglobin levels during pregnancy.